Use of extracorporeal circulation (ECLS/ECMO) for cardiac and circulatory failure –A clinical practice Guideline Level 3. (22nd November 2021) - Assmann, Alexander; Beckmann, Andreas; Schmid, Christof; Werdan, Karl; Michels, Guido; Miera, Oliver; Schmidt, Florian; Klotz, Stefan; Starck, Christoph; Pilarczyk, Kevin; Rastan, Ardawan; Burckhardt, Marion; et al.
Abstract: Aims Worldwide applications of extracorporeal circulation for mechanical support in cardiac and circulatory failure, which are referred to as extracorporeal life support (ECLS) or veno‐arterial extracorporeal membrane oxygenation (va‐ECMO), have dramatically increased over the past decade. In spite of the expanding use and the immense medical as well as socio‐economic impact of this therapeutic approach, there has been a lack of interdisciplinary recommendations considering the best available evidence for ECLS treatment. Methods and Results In a multiprofessional, interdisciplinary scientific effort of all scientific societies involved in the treatment of patients with acute cardiac and circulatory failure, the first evidence‐ and expert consensus‐based guideline (level S3) on ECLS/ECMO therapy was developed in a structured approach under regulations of the AWMF (Association of the Scientific Medical Societies in Germany) and under use of GRADE (Grading of Recommendations Assessment, Development and Evaluation) criteria. This article presents all recommendations created by the expert panel, addressing a multitude of aspects for ECLS initiation, continuation, weaning and aftercare as well as structural and personnel requirements. Conclusions This first evidence‐ and expert consensus‐based guideline (level S3) on ECLS/ECMO therapy should be used to apply the best available care nationwide. Beyond clinical practice advice, remaining important research aspects for future scientific efforts are formulated.